2005
DOI: 10.1177/000348940511400213
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Features and Mitochondrial DNA Sequence in a Large Family Carrying Mitochondrial A1555G Mutation without Use of Aminoglycoside

Abstract: To elucidate the pathophysiological and genetic mechanisms of hearing loss associated with the homoplasmic mitochondrial A1555G mutation in the absence of aminoglycoside exposure, we conducted audiological and genetic analyses on 67 maternally related members of a large Japanese family carrying this mutation. A consistent pattern was evident in the audiograms, with features of sensory presbycusis, cochlear origin at all levels of hearing loss, and a high degree of vulnerability of outer hair cells. That the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…Interestingly, the HI phenotype appeared to be more variable in the fourth generation. The variation of the phenotypes in the present pedigree conforms to that in previous studies, where both affected and nonaffected subjects have been found in sibships [Jaber et al, 1992;Usami et al, 1997;Iwasaki et al, 2000;Matsunaga et al, 2004Matsunaga et al, , 2005. However, our findings also differ from previous studies.…”
Section: Phenotype and Penetrancesupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the HI phenotype appeared to be more variable in the fourth generation. The variation of the phenotypes in the present pedigree conforms to that in previous studies, where both affected and nonaffected subjects have been found in sibships [Jaber et al, 1992;Usami et al, 1997;Iwasaki et al, 2000;Matsunaga et al, 2004Matsunaga et al, , 2005. However, our findings also differ from previous studies.…”
Section: Phenotype and Penetrancesupporting
confidence: 87%
“…In a large Israeli-Arab kindred, most subjects developed a profound HI in infancy or early childhood [Jaber et al, 1992]. In Japanese families neither congenital nor prelingual onset has been identified [Matsunaga et al, 2004[Matsunaga et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of the members who had the m.1555A>G mutation and normal hearing ranged from 1 to 80 years. In a large Japanese pedigree with postlingual hearing loss, Matsunaga et al (2005) described variable phenotypic expression of hearing loss without exposure to aminoglycoside antibiotics. Berrettini et al (2008) studied nine Italian familial idiopathic hearing impaired subjects with the m.1555A>G mutation.…”
Section: Factors Influencing Phenotypic Expression Of Hearing Loss Dumentioning
confidence: 99%
“…Different familial studies revealed that the m.1555A>G mutation carriers are susceptible to hearing loss after treatment with aminoglycosides even at low doses (Gardner et al, 1997;Fischel-Ghodsian et al, 1997;Usami et al, 1997;Estivill et al, 1998;Bai et al 2008). However, in the absence of aminoglycoside exposure the same mutation produces a clinical phenotype that varies considerably among family members and ranges from (i) severe congenital hearing loss, (ii) to moderate progressive hearing loss of later onset, (iii) to completely normal hearing (Prezant et al, 1993;Shoffner et al, 1994;Matthijs et al, 1996;Pandya et al, 1997;Estivill et al, 1998;Matsunaga et al, 2005;Liu et al, 2008). These findings indicate that the m.1555A>G mutation itself is not sufficient to produce a clinical phenotype but requires the involvement of modifier factors for the variable phenotypic expression.…”
Section: Introductionmentioning
confidence: 99%